NSAID Treatment Before and on the Early Onset of Acute Kidney Injury Had an Opposite Effect on the Outcome of Patients With AKI - Wang, Hai; Liu, Tong; Li, Qinglin; Cui, Ruixia; Fan, Xueying; Tong, Yingmu; Ma, Shuzhen; Liu, Chang; Zhang, Jingyao (Frontiers in Pharmacology, 2022)
Background: NSAIDs are one of the most frequently used medications and a risk factor for AKI. However, the optimal time of NSAIDs in patients with AKI is unknown. Methods: A secondary analysis of a multicenter, randomized clinical trial including adult inpatients with acute kidney injury was performed. Univariate, multivariate, and subgroup analyses were used to explore the impact of NSAIDs during the early onset of AKI on the outcome of patients with AKI. Results: A total of 6,030 patients with AKI were enrolled in the study. Following are the findings of the multi-factor analysis: NSAID treatments within 72 and 24 h before the onset of AKI were not associated with AKI progression, dialysis, or discharge from dialysis; only NSAID treatment within the 24-h onset of AKI was associated with these outcomes, and their OR values were independently 1.50 (95% CI: 1.02–2.19, p = 0.037), 4.20 (95% CI: 1.47–11.97, p = 0.007), and 0.71 (95% CI: 0.54–0.92, p = 0.011); only NSAID treatment within the 24-h onset of AKI would decrease the 14-day mortality, and the OR value was 0.52 (95% CI: 0.33–0.82, p = 0.005). The subgroup analysis revealed that in patients with age ≥65 years, CKD (chronic kidney disease), congestive heart failure, hypertension, and liver disease, NSAID treatments within the 24-h onset of AKI would deteriorate the outcome of patients with AKI. Conclusion: Before an early onset of AKI, NSAID treatment might be safe, but during the onset of AKI, even early NSAID treatment would deteriorate the outcome of patients with AKI.